2019
DOI: 10.1002/lary.28302
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of post‐tonsillectomy hemorrhage relative to time of day

Abstract: Objectives Postoperative hemorrhage is a serious complication of tonsillectomy, with secondary bleeding rates affecting up to 0.8% to 3% of patients. Although these bleeds are anecdotally perceived as occurring more frequently at night, the occurrence of hemorrhage relative to the time of day has not been investigated. We measured the frequency of post‐tonsillectomy hemorrhage onset relative to the time of day. Methods We reviewed electronic medical records of all patients who experienced postprocedural hemorr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 33 publications
1
17
0
1
Order By: Relevance
“…For example, one study by Hopkins reported a hemorrhage rate between 0.8 and 3%. 24 However, this study, like most currently found in literature on post-tonsillectomy hemorrhage, focused on two tertiary institutions with a limited amount of surgeons. Contrarily, our study is a composite of national data and includes the rates of various types and levels of institutions and their surgeons nationwide.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study by Hopkins reported a hemorrhage rate between 0.8 and 3%. 24 However, this study, like most currently found in literature on post-tonsillectomy hemorrhage, focused on two tertiary institutions with a limited amount of surgeons. Contrarily, our study is a composite of national data and includes the rates of various types and levels of institutions and their surgeons nationwide.…”
Section: Discussionmentioning
confidence: 99%
“…While it is widely accepted that PTAH can occur up to 14 days after the initial operation, previous studies have found that postoperative hemorrhage most commonly occurred between 5 and 10 days after the initial operation. 11,[15][16][17][18] Our study found that 18% of our cohort had postoperative bleeding after day 10, and 4% presented after day 14. Few studies report on these delayed presentations, particularly the delayed PTAH of 14 to 28 days.…”
Section: Discussionmentioning
confidence: 47%
“…This phenomenon is partly due to hematological parameters including blood viscosity and clotting factors peaking in the morning hours displaying circadian rhythm (25). In a study by Kim et al which examined the variation of bleeding frequency in the day in post-tonsillectomy found that bleeding was observed more frequently at night (26). In our study, the high prevalence of epistaxis occurrence in the evening hours in patients with comorbid conditions such as diabetes mellitus, hemophilia, antiaggregant -anticoagulant medication usage, leukemia and chronic renal failure was found to be statistically significant.…”
Section: Discussionmentioning
confidence: 99%